Characterization of cellulase producing Bacillus and Paenibacillus strains from Thai soils - Ancharida Akaracharanya, Thanawan Taprig, Jaruwan Sitdhipol and Somboon Tanasupawat (Journal of Applied Pharmaceutical Science, 2014)
Seventeen strains of cellulase producing bacteria were isolated from soil samples collected in Nan province, Thailand. They exhibited cellulase activity as a clear zone surrounded their colonies grown on carboxymethyl cellulose (CMC) agar medium ranged from 0.63 to 2.95 cm in diameter. Their hydrolysis capacity values were 1.65 - 7.55. The bacteria isolated were divided into 2 groups and belonged to genus Bacillus and Paenibacillus based on their phenotypic characteristics and chemotaxonomic characteristics such as meso-diaminopimelic in cell wall peptidoglycan and menaquinones of MK-7. Bacillus strains, P3-1 and P4-6 in Group I, produced maximum cellulase at 0.015 U ml-1. Their optimal pH and temperature for enzyme production and enzyme activity were 7.0 and 50 oC, respectively. The strains P3-1 and P4-6 were closely related to Bacillus velesensis LMG 22478T (100% similarity) whereas representative strain, S10-4 in Group II, was closely related to P. cellulositrophicus KCTC 13135T (98.7% similarity) based on 16S rRNA gene sequence. On the basis of their phenotypic, chemotaxonomic characteristics and phylogenetic analysis of 16S rRNA gene sequence, the strains P3-1 and P4-6 were identified as B. velesensis and the strain S10-4 was a novel species in the genus Paenibacillus.
Keywords: Cellulase, Bacillus, Paenibacillus, 16S rRNA gene sequence, Thai soil